Gender dan Budaya: Citra Perempuan pada Cerpen “Perempuan Itu Pernah Cantik” karya Mashdar Zainal - Mazidah, Nadia Nur; Zarnubi, Muhammad; Surur, Misbahus (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2026)
In married life, women often experience a significant transition that can leave them in shock. This study aims to describe the portrayal of women in the household in the short story